â€œVirginityâ€, Search of Pleasure in Female Body: Psychoanalysis of Sexual Violence in Perpetrators - Poerwandari, Elizabeth Kristi (Jurnal Perempuan, 2016)
This article focuses on the rationalization of perpetrators of sexual offense against women, in a form of re-analysis of data gathered from one police resort in Greater Jakarta. The article presents the data of 9 (nine) suspects who were reported to the police by their girlfriends or the family of their girlfriends. Sexual offense toward women could not be separated from the lower bargaining position of women, as well as the views of sexuality which cornering women. Marrying the victim to the perpetrator is one practice that is still popular to solve the problem, which makes the situation worse for the victim. This also spread the socialization and practices of mean and irresponsible behavior by perpetrator or potential perpetrator. Double standard views on sexuality lead to the vulnerable situation of women, and make it more difficult to fight for justice on the issue of sexual offense. The double standard is also dominating the mind of the general public and even the public official. Therefore, the Law needs to view sexuality and sexual violence in a comprehensive understanding, with gender justice perspectives which also protect children.